1994
DOI: 10.1002/jlb.55.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of prostaglandin endoperoxide synthase-2 during mouse macrophage activation

Abstract: We investigated regulation of macrophage prostaglandin production during activation by interferon gamma (IFN-gamma) and lipopolysaccharide (LPS). An in vitro model was established using the mouse macrophage-like cell line RAW 264.7. Cells were cultivated in the presence of IFN-gamma and LPS for up to 48 h and changes in the secretion of nitric oxide (NO.) and tumor necrosis factor alpha (TNF-alpha) were observed as activation markers. Under these conditions a prompt and strong increase in PGE2 production was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…DISCUSSION IFN-␥ has been reported to regulate the expression of COX-2 in several cell systems. In human bronchial epithelial cells and macrophages (42,62), IFN-␥ induces COX-2, while it has no effect in osteoblast and smooth muscle cells (41) and inhibits COX-2 expression in microglial cells (63). In this study, we demonstrate that in NHEK IFN-␥, treatment causes a dramatic induction in the expression of COX-2, while COX-1 expression is inhibited.…”
Section: Importance Of Cre/atf/e-box In the Transcriptional Regulatiomentioning
confidence: 62%
“…DISCUSSION IFN-␥ has been reported to regulate the expression of COX-2 in several cell systems. In human bronchial epithelial cells and macrophages (42,62), IFN-␥ induces COX-2, while it has no effect in osteoblast and smooth muscle cells (41) and inhibits COX-2 expression in microglial cells (63). In this study, we demonstrate that in NHEK IFN-␥, treatment causes a dramatic induction in the expression of COX-2, while COX-1 expression is inhibited.…”
Section: Importance Of Cre/atf/e-box In the Transcriptional Regulatiomentioning
confidence: 62%
“…In addition to inducing the expression of several genes, incubation of macrophages with IFN-␥ enhances their responsiveness to LPS (10,24). To determine whether PKC-␣ plays a role in the regulation of IFN-␥-induced responses, we have measured the induction of COX-2 mRNA accumulation and protein synthesis in control RAW 264.7 cells and in the DN PKC-␣-overexpressing clones B1 and C2 in response to 100 U/ml IFN-␥ alone or in combination with 100 ng/ml LPS.…”
Section: Effect Of Dn Pkc-␣ Overexpression On Cox-2 Expression Followmentioning
confidence: 99%
“…In human and murine macrophages, COX-2 expression is induced by LPS, IL-1, and phorbol esters (6 -9). Studies with the murine macrophage cell line RAW 264.7 indicated that accumulation of COX-2 mRNA can be induced by a combination of IFN-␥ and LPS but not by IFN-␥ alone (10). In addition to soluble mediators, pathogens such as the intracellular parasite Leishmania donovani can increase synthesis of PGE 2 , possibly by inducing alterations in the COX pathway (11,12).…”
mentioning
confidence: 99%
“…COX-1 is expressed constitutively in most tissues and may be responsible for housekeeping functions (4). In contrast, COX-2 is not detectable in most normal tissues or resting immune cells, but its expression can be induced by endotoxin, cytokines, growth factors, and carcinogens (5)(6)(7).…”
mentioning
confidence: 99%
“…Macrophage activation is accompanied by a significant increase in COX-2 expression, whereas levels of COX-1 remain unchanged (7,8). In vivo macrophage COX-2 immunoreactivity is a characteristic finding in the synovium of patients with osteoarthritis as well as in other forms of inflammation, whereas COX-1 expression typically remains unchanged (9,10).…”
mentioning
confidence: 99%